UPTAKE OF DISSOLVED CD BY BIOGENIC AND ABIOGENIC ARAGONITE: A COMPARISON WITH SORPTION ONTO CALCITE - Prieto M.; Cubillas P.; Fernandez-Gonzalez A. (My University, 2003)
The uptake of Cd2+ by aragonite and calcite is investigated by combining macroscopic measurements with some qualitative sorption experiments performed in a hydrogel medium. Both biogenic and abiogenic aragonites were studied in order to evaluate the process on materials with different textures. Assuming that sorption occurs by surface precipitation of metal-bearing solids, the gel produces a drastic decrease in the nucleation density, which allows for the precipitation of crystallites that are large enough to be analysed by scanning electron microscopy and characterized by glancing-incidence X-ray techniques. The macroscopic study reveals that aragonite is a powerful sorbent for cadmium in aqueous environments. Microscopic observations indicate that cadmium is sorbed onto aragonite by surface precipitation of (Cd, Ca)CO3 solid solutions with a calcite-type structure. The precipitating individuals grow randomly oriented on the surface to reach sizes in the micrometre range. As a consequence, the concentration of cadmium in the aqueous solution decreases dramatically to values controlled by the low solubility of the cadmium-rich end member. This mechanism involves simultaneous dissolution-crystallization and is the same for both abiogenic and biogenic aragonites, the only difference being a result of the higher specific surface area of the biogenic starting material. Long-term uptake of cadmium by calcite occurs through a similar dissolution-crystallization mechanism, the final outcome being virtually the same, that is, surface precipitation of (Cd,Ca)CO3 solid solutions. In this case, however, substrate and precipitate are isostructural and the process occurs by oriented overgrowth of thin lamellar crystallites, which spread to quickly cover the surface by a layer a few nanometers thick. This epitaxial layer armors the substrate from further dissolution, so that the process stops when only a small amount of cadmium has been removed from the fluid. As a result, the ''sorption capacity'' of calcite is considerably lower than that of aragonite. The study illustrates reaction pathways and ''partial'' equilibrium endpoints in surface-precipitation processes involving solid solutions.